Pengaruh Penggunaan Gadget Terhasap Akhlak Peserta Didik Kelas V MIS Hidayatusshibyan: Pendidikan Islam - edy edy (Edusifa: Jurnal Pendidikan Islam, 2023)
Gadget users in this modern era are not only parents and teenagers, most elementary school  children can already operate gadgets as entertainment media that make them addicted so that the  consequences of addiction can change children's morals to be bad. The purpose of this study was to  determine the effect of using gadgets on the morals of the fifth grade students of MIS Hidayatusshibyan.  This type of research is quantitative research. The results showed that there was a negative influence  on the use of gadgets on the morals of fifth grade students at MIS Hidayatusshibyan. This is evidenced  by the results of the tabulation of the calculation of the questionnaire which is included in the fairly  strong category. This correlation value can be seen from the results of the interpretation of the rxy  value of 0.535 which is located between 0.40 to 0.599 with a fairly strong correlation interpretation,  the "r" count is greater than the "r" table both at the 5% significance level of 0.413 and the significant  level 1 % of 0.526. The morals of students are influenced by gadgets by 29% while 71% are influenced  by other factors outside the variables in the research used. Keywords: Gadget Morale, Student